Anatomy of Zetela alphonsi Vilvens, 2002 casts doubt on its original placement based on conchological characters (Mollusca, Solariellidae) - Schwabe, E; Heβ, M; Sumner-Rooney, L; Sellanes, J (Zoologische Staatssammlung Muenchen, 2017)
Zetela is a genus of marine gastropods belonging to the family Solariellidae (Vetigastropoda, Trochoidea). The species Zetela alphonsi Vilvens, 2002 was originally described using classical conchological characters from samples obtained from deep water off Chiloé, Chile, but no other features were recorded in the original description. In the present paper, taxonomically relevant characters such as the operculum, radula, and soft part anatomy are illustrated and described for the first time from a specimen of Zetela alphonsi from a new locality, a methane seep area off the coast of central Chile. We find that many features differ substantially from other members of the genus, including several which deviate from characters that are diagnostic for Zetela. Zetela alphonsi also lacks retinal screening pigment, giving the appearance of eyelessness from gross examination. Although pigmentation loss has been reported in other deep sea genera, this feature has not been reported in any other members of Zetela. We reconstructed a tomographic model of the eye and eyestalk, and demonstrate that a vestigial eye is still present but externally invisible due to the loss of pigmentation. Based on these new morphological characters, particularly observations of the radula, we suggest that the current placement of this species in the genus Zetela should be reconsidered.